DNAzyme‐Assisted Nano‐Herb Delivery System for Multiple Tumor Immune Activation. Issue 45 (26th September 2022) - Du, Shiyu; Chen, Chao; Qu, Suchen; Song, Hongxiu; Yang, Jingjing; Li, Yayao; Liu, Kunguo; Lu, Qianglan; Luo, Wen; Wang, Runtian; Guan, Xiaoxiang; Song, Yujun; et al.
Abstract: As a promising therapeutic strategy against cancer, immunotherapy faces critical challenges, especially in solid tumors. Immune checkpoint blockade therapy, particularly blocking the interaction of the programmed cell death 1 (PD1)‐PD1 ligand 1 (PD‐L1) axis, can reverse the suppression of T cells so as to destroy tumor cells and exert antitumor effects. Here, a strategy of multiple activation of immune pathways is developed, to provide supporting evidence for potential antitumor therapies. Briefly, a pH/glutathione responsive drug‐loading hollow‐manganese dioxide (H‐MnO2 )‐based chlorine6 (Ce6)‐modified DNAzyme therapeutic nanosystem for the combination of gene therapy and immunotherapy is established. The H‐MnO2 nanoparticles could efficiently deliver the DNAzyme and glycyrrhizic acid (GA) to enhance the tumor target effects. In the tumor microenvironments, the biodegradation of H‐MnO2 via pH‐induced hydrolyzation allows the release of guest DNAzyme payloads and host Mn 2+ ions, which serve as PD‐L1 mRNA‐targeting reagent and require DNAzyme cofactors for activating gene therapy. In addition, Mn 2+ is also associated with the immune activation of thcGAS‐STING pathway. Auxiliary photosensitizers Ce6 and GA could produce reactive oxygen species, resulting in immunogenic cell death. Overall, this study provides a general strategy for targeted gene inhibition and GA release, which is valuable for the development of potential tumor immunotherapies. Abstract : A pH/glutathione responsive drug‐loading hollow‐manganese dioxide (H‐MnO2 )‐based chlorin e6‐modified DNAzyme therapeutic nanosystem is established for the combination of gene therapy and immunotherapy. This study provides a general strategy for targeted gene inhibition and GA release, which is valuable for the development of potential tumor immunotherapies.